Difference between T-SQL and the Relational Model - Lozic, Davor; Simec, Alen (TEM Journal, 2015)
T-SQL, dialect of SQL, is a language used for a relational database management system (primarily Microsoft’s SQL Server), which in turn is based on the relational model. Understanding some of the key foundation principals can help in a better understanding of the language. This paper introduces basics of the relational model and the difference between the relational model and the actual T-SQL implementation.Several tightly related topics like predicates, relations, and common misconceptions about databases are also discussed.